The effect of lactation number on milk production and reproduction in Holstein cows - Özçelik, M; Arpacik, R (Scientific Technical Research Council Turkey, 2000)
This study was carried out to investigate the effect of lactation number on milk production and reproduction. Data on milk and reproductive traits in the first five lactations of Holstein cows reared at Bala State Farm were used. The following characteristics were studied: milk yield, lactation duration and dry period. The following reproductive traits were also studied: number of inseminations per conception, service period, gestation period and calving interval. According to the results, in general milk yield increased but lactation duration decreased with increasing lactation number. However, no linear relationship was determined between dry period and lactation number. The effect of lactation number on milk yield and dry period was found to be statistically significant (P<0.001), as well as on carving interval (P<0.05). Insemination number, service period and calving interval decreased with increasing lactation number after the second lactation. The best milk and reproductive performance were obtained in the fourth lactation.
Keywords: Holstein; lactation number; milk and reproductive traits